Temperature-sensitive protein expression in protocells. Issue 45 (16th May 2019) - Jia, Haiyang; Heymann, Michael; Härtel, Tobias; Kai, Lei; Schwille, Petra
Abstract : We engineered a synthetic temperature regulation toolbox to enable protocells to sense and respond to heat, utilizing RNA thermometers. Abstract : We engineered a synthetic temperature regulation toolbox to enable protocells to sense and respond to heat, utilizing RNA thermometers. The thermo-sensitive protocells were generated by encapsulating temperature feedback transcription/translation machinery in droplets. Based on these temperature-sensing devices, the protocells can be operated with logic AND gates, differentially processing temperature stimuli into biological signals.